Effects of calcium channel blockers and halotane on albino hepatocytes - Erhan, O.L.; Onal, A.; Ozercan, R.; Oysul, B.; Ugur, F.; Gezen, M.R. (My University, 1992)
[Abstract Not Available]
Keywords: calcium channel blocking agent; halothane; inhalation anesthetic agent; nicardipine; animal experiment; animal tissue; article; calcium homeostasis; cytotoxicity; liver cell; liver protection; liver toxicity; nonhuman; rat